Analisis Peran Komite Sekolah dalam Pengelolaan Sarana dan Prasarana di SD Gugus V Kecamatan Sibulue Kabupaten Bone - Nana Karlina; Muliadi Muliadi; Sudarto Sudarto (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
Abstract; The problem in this study is that the role of the school committee in managing school facilities and infrastructure is still not optimal. This research is a type of descriptive qualitative research that describes the role of the school committee as a giver of considerations, supporters, controllers and mediators in Elementary School cluster V, Sibulue District, Bone Regency. The subjects in this study were the head of the school committee, the principal, and the teacher. data collection was done by interview method. The results of this study 1) As a giver of consideration, namely preparing a joint work program with the school and providing input in the elimination of facilities and infrastructure. 2) As a supporter, namely providing support in the form of energy, thought and finance, 2) As a controller, namely monitoring the funds that have been allocated for repairing school facilities and checking the condition of facilities and infrastructure, 3) As a mediator, namely conveying public opinion to the school, and as a bridge for funds from students' parents and the community. From the results of this study, it can be concluded that the school committee has carried out its role but still needs to be optimized, such as providing encouragement and motivation to parents and the community to provide support in helping to improve the quality of facilities and infrastructure. With the optimal role of the school committee, it is very helpful for schools to improve the quality of school facilities and infrastructure.Keywords: Role; School Committee; Facilities and Infrastructure